Recessions and Occupational Match Quality: The Role of Age, Gender, and Education - John T. Addison; Liwen Chen; Orgul D. Ozturk (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Although the adverse labor market effects of economic recessions have been well documented, a notable omission in the literature is how recessions impact workers' job match quality. This paper considers the short and longer-term losses in productivity associated with the job changing brought in train by the two most recent recessions. Changes in match quality are the mechanism, with dislocated workers being reemployed in jobs for which they are more mismatched. Using monthly data from the 1979 and 1997 cohorts of the National Longitudinal Survey of Youth and the Current Population Survey (CPS), we document direct changes in occupational match quality and the associated changes in wages. We first investigate how workers' match qualities change over the lifecycle and report that the total amount of mismatch averaged over all workers of the younger cohort actually decreased through time. For the older cohort, we then explore the role of age, education, gender, and occupational task groups. Economic recessions are shown to disproportionately harm the match quality of mid-aged workers versus that of young workers; to have more serious consequences for the match quality of men than women, especially highly educated men; and lead to occupational polarization, thereby amplifying the skill mismatch of mid-aged workers.
Keywords: E24; J24; J63; 330; recessions; match quality; mismatch; wage loss; mid-career effects; mancessions; downskilling